OBSERVAÃ‡Ã•ES SOBRE O CONTROLE DO ÃCARO ð˜›ð˜¦ð˜µð˜³ð˜¢ð˜¯ð˜ºð˜¤ð˜©ð˜¶ð˜´ ð˜¥ð˜¦ð˜´ð˜¦ð˜³ð˜µð˜°ð˜³ð˜¶ð˜® Banks, 1900 COM DIVERSOS DEFENSIVOS EM BANANEIRA DA VARIEDADE DE NANICÃƒO - Setten, M. L.; Melo, L. A. Silveira; Nakano, O.; Flechtmann, C. H. W. (REVISTA DE AGRICULTURA, 2020)
OBSERVAÃ‡Ã•ES SOBRE O CONTROLE DO ÃCARO ð˜›ð˜¦ð˜µð˜³ð˜¢ð˜¯ð˜ºð˜¤ð˜©ð˜¶ð˜´ ð˜¥ð˜¦ð˜´ð˜¦ð˜³ð˜µð˜°ð˜³ð˜¶ð˜® Banks, 1900 COM DIVERSOS DEFENSIVOS EM BANANEIRA DA VARIEDADE DE NANICÃƒO